Analisis Pengaruh Ukuran Perusahaan, Profitabilitas, Solvabilitas Dan Laba Rugi Perusahaan Terhadap Audit Delay - Hizbiatul Maulani; Endang Kartini; Sofiati Wardah (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This study aims to examine the effect of company size, profitability, solvency, and company profit and loss on audit delay in mining companies listed on the Indonesia Stock Exchange in 2020-2022. The population of this study are mining companies listed on the Indonesia Stock Exchange, totaling 47 companies. The sampling technique used purposive sampling method. The number of companies used as sampled in this study were 19 companies with an observation period of three years. The total sample obtained is 57 financial statements. Testing the hypothesis using multiple linier regression technique. The partial test results show that Firm size has a significant effect on audit delay, profitability has no effect on audit delay, solvency has no effect on audit delay, company profit and loss has a significant effect on audit delay. The simultan test results show that firm size, profitabilit, solvency and company profit and loss have a significant effect on audit delay.